Potential of Grocery Bags Plastic Waste as a Fuel Substitute for Fossil-Based Fuels: A Characterization Study on the Non-Catalytic Low-Temperature Pyrolysis Process - Eka Daryanto; Dina Ampera; Zulkifl Matondang; Janter Pangaduan Simanjuntak; Bisrul Hapis Tambunan; Mohamad Yusof Idroas; Nurin Wahidah Binti Mohd Zulkifli; Mohamad Zamri Zainon; Riduwan Riduwan (Automotive Experiences, 2024)
Currently, pyrolysis is the primary choice for addressing the significant problems caused by plastic waste. Temperature and catalysts are the main parameters in pyrolysis. However, using catalysts can become a serious problem when scaling up production capacity, as the process can become more complex and expensive due to the high cost of catalysts. Without a catalyst, the required pyrolysis temperature must be sufficiently high to achieve high-quality pyrolytic fuel oil. In this work, plastic grocery bag is pyrolyzed followed by distillation to produce a liquid similar to conventional fuel, called distillate plastic fuel. Non-catalyst and low-temperature pyrolysis was performed at a single temperature of 350 °C, followed by distillation at temperatures of 250 °C and 350 °C to determine the effect of distillation temperature on the chemical properties of the obtained distilled fuel. Elemental and composition analyses were conducted using the GCMS method. Results indicated that the chemical properties and composition of distilled plastic fuel are similar to diesel fuel with a heating value of approximately 43.362 to 44.364 MJ/kg.